2021
DOI: 10.1002/mp.14843
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Single‐pulse beam characterization for FLASH‐RT using optical imaging in a water tank

Abstract: High dose rate conditions, coupled with problems related to small field dosimetry, make dose characterization for FLASH-RT challenging. Most conventional dosimeters show significant dependence on dose rate at ultra-high dose rate conditions or fail to provide sufficiently fast temporal data for pulse to pulse dosimetry. Here fast 2D imaging of radioluminescence from a water and quinine phantom was tested for dosimetry of individual 4 μs linac pulses. Methods: A modified clinical linac delivered an electron FLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Rahman et al. used a fast photomultiplier tube‐based Cherenkov detector with a 2‐ns sampling rate, two orders of magnitude above that presently achieved using the Hyperscint 23,45,46 . This detector allows the resolution of single linac pulses and the measurement of 2‐D dose distributions through a water tank delivered at 60 Hz (100 MU/min using photons).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahman et al. used a fast photomultiplier tube‐based Cherenkov detector with a 2‐ns sampling rate, two orders of magnitude above that presently achieved using the Hyperscint 23,45,46 . This detector allows the resolution of single linac pulses and the measurement of 2‐D dose distributions through a water tank delivered at 60 Hz (100 MU/min using photons).…”
Section: Discussionmentioning
confidence: 99%
“…Rahman et al used a fast photomultiplier tubebased Cherenkov detector with a 2-ns sampling rate, two orders of magnitude above that presently achieved using the Hyperscint. 23,45,46 This detector allows the resolution of single linac pulses and the measurement of 2-D dose distributions through a water tank delivered at 60 Hz (100 MU/min using photons). By using a small region of interest in their 2-D dosimeter, the authors were also able to resolve signals acquired at 360 Hz (600 MU/min) to monitor beam output.…”
Section: Discussionmentioning
confidence: 99%
“…Images from a time‐gated camera for acquisition of each Linac pulse (a), from emission in a water phantom for depth dose, 72 and on the surface of a board for lateral profile 73 . The ability to image this light signal during each pulse (c) shows the value for pulse‐to‐pulse verification of delivery.…”
Section: Online Imaging and In Vivo Dosimetrymentioning
confidence: 99%
“…Lateral and depth profile images are possible to fully quantify the 3D dose distributions in water tanks, 23,70 while limited to surface images in applications to patients. Applicability to protons and light ions, for which Cherenkov and luminescence emissions have recently been reported, interestingly below the expected theoretical threshold limits, 71 could further benefit from F I G U R E 2 Images from a time-gated camera for acquisition of each Linac pulse (a), from emission in a water phantom for depth dose, 72 and on the surface of a board for lateral profile. 73 The ability to image this light signal during each pulse (c) shows the value for pulse-to-pulse verification of delivery.…”
Section: Optical Imaging For In Vivo Dosimetrymentioning
confidence: 99%
“…The literature on pulse-by-pulse detection systems is scarce, and mainly focused on scintillator- and fiber-optics-based dosimetry [ 28 , 29 ]. As for diamond-based solutions, Velthuis et al [ 30 ] reported on a prototypal system for single-pulse measurements; however, this exhibited a response time of several hundreds of μs and required relatively complex front-end analogue electronics.…”
Section: Introductionmentioning
confidence: 99%